MODAL ANALYSIS OF HYBRID ADAPTATIVE BEAMS - Ferreira, Guilherme Vaz; Levy Neto, Flaminio (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Smart or adaptative structures are those capable to perform some special functions when stimulated externally. In the context of this type of structure, hybrid adaptative composite beams, reinforced with active Ni-Ti filaments, were simulated in the present work. Such beams may be adopted for vibration control, exploring the possibility of changing their bending stiffness by means of controlling the temperature of the shape memory alloy filaments. The main objective of this paper is to present, for a free-free boundary condition, the vibration modes and their frequencies obtained analytically and numerically for prismatic beams, which incorporate nineteen layers of epoxy reinforced with chopped E-glass mat (17 plies), and two symmetric active plies (A) embedded with up to four Ni-Ti wires each (2+A+13+A+2). One particular aspect of this investigation is to verify how the natural frequency of the beams changes, when an electric current passes through the Ni-Ti wires and elevates their temperature from 25 ºC to 69 ºC, converting 100% of the Ni-Ti wires into the more rigid austenitic phase. In order to verify the accuracy of the analytical method, it was compared with two numerical models based on the finite element method. The maximum differences between the methodologies, in module, was 4.50%.